Adherence to Palestinian Guidelines in Active Management of the Third Stage of Labor to Prevent Postpartum Hemorrhage: A Study at Shifa and Nasser Medical Complexes in Gaza Strip - Alkahlout, Duaa; Alzraiy, Rawan; Ghorab, Samar Abu; Ebaid, Eman; Sultan, Meran Abu (International Journal of Innovative Research in Medical Science, 2024)
Background: Postpartum hemorrhage (PPH) is a leading cause of maternal morbidity and mortality. This study assesses adherence to Palestinian guidelines for the active management of the third stage of labor to prevent PPH in the Gaza Strip's Al-Shifa and Nasser Medical Complexes. Methods: A prospective, descriptive, and cross-sectional study was conducted. A convenience sample of 50 parturients who met the inclusion criteria and agreed to participate was recruited. Data were collected at delivery through close observation of vaginal births. Risk factors for PPH and adherence to active management protocols were documented using standardized checklists and questionnaires. Descriptive statistics summarized the findings, and ethical considerations were strictly adhered to. Results: The mean age of participants was 25.9 years (SD: 5.86). Key risk factors included 66% (33 out of 50) having a BMI above normal, 8% (4 out of 50) not receiving antenatal care, and 48% (24 out of 50) having anemia. Previous obstetric complications were noted: 10% (5 out of 50) had a history of PPH, 16% (8 out of 50) had previous cesarean sections, and 14% (7 out of 50) delivered babies with a birth weight over 4.5 kg. All participants received Oxytocin 10-unit IM or IV with the delivery of the anterior shoulder or immediately after fetal delivery. However, 48% (24 out of 50) did not undergo delayed cord clamping for 1-3 minutes, primarily due to fetal distress. Controlled cord traction and initial uterine massage were performed in all cases, but repeated uterine massage every 15 minutes for the first hour was omitted in 54% (27 out of 50) of cases due to staff shortages. Only 6% (3 out of 50) received Methergine IM due to its unavailability, and 41% (20 out of 50) were not given Oxytocin 40 units. Conclusion: The study identified significant adherence to certain PPH prevention protocols, but highlighted gaps in practice, such as inconsistent delayed cord clamping and repeated uterine massage, primarily due to resource constraints and staffing issues. Addressing these gaps by ensuring the availability of necessary medications, improving staffing levels, and reinforcing adherence to guidelines is crucial for enhancing maternal health outcomes in these settings.